Praktik Green Supply Chain Management dan Kinerja Bisnis pada Coffeeshop: Kepuasan Kerja Karyawan sebagai Variabel Mediasi - Atos, Saridha; Zaitul, Zaitul (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
In the era of business sustainability, the adoption of Green Supply Chain Management (GSCM) practices has become a crucial strategy to enhance competitive advantage, even in small-scale service sectors such as coffeeshops. This study aims to examine the direct impact of GSCM practices on business performance and to assess the mediating role of employee job satisfaction in this relationship. A quantitative approach was employed by surveying 30 employees from various coffeeshops in Padang City, Indonesia. Data were analyzed using Structural Equation Modeling with the Partial Least Squares (PLS-SEM) method. The results indicate that GSCM practices have a positive and significant effect on business performance. Furthermore, GSCM also significantly influences employee job satisfaction. However, the mediating effect of employee job satisfaction on the relationship between GSCM and business performance is not statistically significant. The model explains 63.4% of the variance in business performance and 24.9% in employee job satisfaction, indicating strong explanatory power for business outcomes but limited predictive relevance for job satisfaction. These findings underscore that while GSCM directly contributes to improving operational and reputational performance, efforts to enhance employee satisfaction must be reinforced to maximize overall organizational effectiveness. This study provides valuable insights for coffeeshop managers and SMEs, encouraging strategic integration of sustainability practices with human resource development to achieve sustainable business growth.